(untitled) (Journal of Enam Medical College, 2014)
Background: Rana Plaza collapse is the worst and deadliest man-made industrial disaster in the history of garment sector in the world. Around 1200 people died and thousands more were injured. Most of the victims of the disaster were treated in Enam Medical College Hospital (EMCH). We conducted this study to give an overview on the disaster victims and services provided by EMCH. Objective: The study was done to observe the length of time between accident and admission in EMCH, length of time between admission and discharge, to observe the numbers, types and sites of injuries to the victims, medical measures given to the victims and finally to observe the status of the victims at the time of discharge. Materials and Methods: This descriptive type of observational study was carried out among the victims of Rana Plaza tragedy during the period of May to October 2013. All admitted patients in EMCH were included in the study. Purposive nonprobability sampling technique was applied in this research work. Data were collected from the hospital record. After collection, data were manually compiled, edited and analyzed. Results: Among 621 victims treated in different wards, 276 (44.45%) were admitted to the hospital on the day of accident. Among the admitted patients, 255 (41.06%) stayed in the hospital for 1–3 days,133 (21.42%) for 4–7 days and 88 (14.17%) for more than 10 days. Fracture and dislocation were present in 32.70% patients, lacerated injury in 18.20%, abrasion in 15.78%, bruise in 13.53%, incised wound in 15.45% and punctured wound in 4.34% patients. Single injury was present in 56.68% and rest had multiple injuries. Lower limbs were the most (33.01%) affected part of the body followed by head and neck (22.06%), upper limbs (18.52%), thorax (17.55%) and abdomen (8.86%). Two hundred seventy two patients (43.80%) were improved after treatment and 56 (9.02%) were fully cured; 23.83% of the victims were referred to higher medical centers for special measures. Conclusion: The collapse of Rana Plaza has fueled a greater call for reform and safety in garment industry. At the same time, all health care centers should adopt a broad-based approach to disaster-preparedness by providing a framework to ensure a well-coordinated response to mass casualty event. DOI: http://dx.doi.org/10.3329/jemc.v4i1.18066 J Enam Med Col 2014; 4(1): 31-35